Pendekatan Konstrutivisme dalam Pembelajaran Berbasis Case Method pada Siswa SMAN 2 Palu - Nurwahyuni, Nurwahyuni; Rasido, Ikhlas; Wahyuningsi, Nur Eka; Silalahi, Micha Felayati; Hasan, Hasan (Jurnal Ilmiah Dikdaya, 2024)
This research aims to apply a constructivist approach in innovative learning based on the case method to improve students' critical thinking skills at SMAN 2 Palu. Through a constructivist approach, it is hoped that students can be stimulated and given the opportunity to learn, think innovatively, and optimize their potential. The application of the constructivist approach in case method-based learning is expected to encourage the active participation of students at SMAN 2 Palu, enabling them to form their own knowledge through developing critical thinking skills. This research is quantitative research with data collection methods using critical thinking skills questionnaires which are analyzed using descriptive, paired analysis. samples test, and simple regression analysis with the statistical assistance of the SPSS version 26 program. The results of data analysis show that the sig (2-tailed) value is 0.000 < 0.005. This means that the application of a constructivist approach in case method-based learning can improve the critical thinking skills of students at SMAN 2 Palu. The results of descriptive analysis also show that the posttest average for thinking skills is greater than the pretest, namely the posttest average value is 80.97 and the pretest average value is 68.70.